Focusing on the Latest Advances in Surgical Techniques for Cancer Treatment, Including Organ-Sparing Surgery and Personalized Treatments - Sattar, Sabah; Ali, Mansab; Badar, Quratulain; Wassan , Nadir Ali; Gul, Hassam; Aqueel , Malaika (Indus Journal of Bioscience Research, 2025)
This study aims to compare the outcomes of organ-sparing surgery and radical surgery in cancer treatment, focusing on survival rates, recovery times, and post-operative complications. A quantitative analysis was conducted on a sample of 105 cancer patients across Punjab, Pakistan, using descriptive statistics, ANOVA, Chi-square tests, and regression analysis. The results revealed that organ-sparing surgery resulted in better survival rates and shorter recovery times compared to radical surgery. However, there were no significant differences in post-operative complications between the two surgical approaches. Regression analysis indicated that age and tumor size significantly impacted survival rates and recovery times, with older age and larger tumor size being associated with worse outcomes. Chi-square tests showed no significant relationship between surgical method and recurrence rates, suggesting that surgical approach does not significantly affect recurrence in this sample. These findings highlight the importance of individualized treatment plans and the growing role of organ-sparing surgery in improving patient outcomes. This research reinforces the growing recognition of organ-sparing surgery as a highly effective cancer treatment, offering improved survival rates and quicker recovery compared to radical surgery. Patients undergoing organ-sparing procedures experience a more favorable post-operative course, with better preservation of organ function and quality of life, particularly in cancers such as breast, kidney, and rectal cancer. While organ-sparing surgery provides outcomes comparable to radical interventions, surgical selection must consider factors like tumor size, site, and extent. Older age and larger tumors were associated with worse survival and recovery, emphasizing the need for individualized treatment. Advancements in robotic surgery, minimally invasive techniques, and personalized medicine will further refine cancer surgery, improving patient outcomes globally.